Native Wine Grapes of Italy. - D'Agata, Ian (University of California Press, 2014)
Mountainous terrain, volcanic soils, innumerable microclimates, and an ancient culture of winemaking influenced by Greeks, Phoenicians, and Romans make Italy the most diverse country in the world of wine. This diversity is reflected in the fact that Italy grows the largest number of native wine grapes known, amounting to more than a quarter of the world's commercial wine grape types. Ian D'Agata spent thirteen years interviewing producers, walking vineyards, studying available research, and tasting wines to create this authoritative guide to Italy's native grapes and their wines. Writing with.